Caracterização magnética de aço com a superfície endurecida - Silva, Gustavo Rodrigues da (My University, 2014)
This work investigates the magnetic properties (hysteresis loop and Barkhausen noise) in some steels (ABNT 1045, 1050 and 1548) whose surfaces had been hardened by induction. The goal was to develop a non-destructive test procedure to determine the thickness of the hardened layer, thus avoiding the need to perform (destructive) measurements of the microhardness. Measurements of the magnetic susceptibility showed a peak (ferrite) around 800 A / m and other (martensite) at around 3500 A / m. Therefore, a correlation was sought between the peak amplitude of ferrite with the thickness of hard layer on the surface. For this purpose sensors were developed to measure Barkhausen noise as well as a filter for signal processing. It was possible to correlate measurements of microhardness with some features observed in magnetic measurements, for example, the amplitude of the Barkhausen noise and magnetic field of peak Barkhausen signal. Thus, a relationship was found between the amplitude of the Barkhausen noise and the thickness of the surface layer. It would be desirable to supplement these with other measurements and suggestions for further work are detailed.
Neste trabalho foram investigadas as propriedades magnéticas (curva de histerese e ruído Barkhausen) de alguns aços (ABNT 1045, 1050 e 1548) cujas superfícies foram endurecidas por indução. O objetivo era de desenvolver um ensaio não-destrutivo para determinar a espessura da camada endurecida, assim evitando a necessidade de realizar medidas (destrutivas) de microdureza. Medidas da susceptibilidade magnética mostraram um pico (ferrita) em torno de 800 A/m e outro (martensita) em torno de 3500 A/m. Assim procuramos correlacionar a amplitude do pico de ferrita com a espessura da camada dura na superfície. Para esta finalidade foram desenvolvidos sensores para medir ruído Barkhausen e um filtro para o processamento do sinal. Foi possível correlacionar medidas de microdureza com algumas características observadas nas medições magnéticas, como, por exemplo, a amplitude do sinal de ruído Barkhausen e o campo magnético do pico do sinal Barkhausen. Deste modo, encontrou-se uma relação entre a amplitude do ruído Barkhausen e a espessura da camada superficial. Seria desejável complementar essas medidas com outras e sugestões para uma continuação do trabalho são detalhadas.
Keywords: Engenharia de materiais e metalúrgica; Aço - carbono; Curva de histerese; Ruído Barkhausen; Microdureza; Testes de dureza; Materiais magnéticos; Carbon steel; Hysteresis curve; Barkhausen noise; Microhardness; Hardness tests; Magnetic monopoles